Immune Modulation Through Stereotactic Radiotherapy: The Role of TBX21, GATA-3, FoxP3, and RORɣt - Aybala Nur Ucgul; Huseyin Bora; Gizem Yaz Aydin; Ozlem Gulbahar; Ummu Habibe Koken (Medicina)
Background and Objectives: Stereotactic radiotherapy enhances local tumor control by delivering high doses directly to the tumor. It is thought to activate the immune system via T-cells, possibly creating a systemic response. This study aims to evaluate stereotactic body radiotherapy’s (SBRT) impact on the immune system by measuring T-cell transcription factors, such as TBX21, GATA-3, FoxP3, and RORɣt. Materials and Methods: Peripheral blood samples were collected from 103 patients before SBRT and from 66 patients two months post-treatment. We measured transcription factors TBX21, GATA-3, FOXP3, and RORγt using ELISA, and performed a complete blood count and C-reactive protein analysis to rule out infections. Statistical analyses included paired t-tests and correlation analyses to assess changes before and after treatment. Results: Post-treatment, significant reductions were observed in TBX21 (Th1), GATA-3 (Th2), and FOXP3 (Treg), while RORɣt (Th17) remained stable but trended higher in lung cancer patients. No correlations were found with demographic factors. However, TBX21 levels were significantly related to the planning target volume (PTV) and biologically effective dose (BED10) in the lung region. Larger PTVs (≥16.5 cc) and higher BED10 doses (≥100 Gy) were linked to smaller reductions in TBX21 (p = 0.008, p = 0.04) and increased RORɣt levels (p = 0.01). Conclusions: Stereotactic radiotherapy reduces immunosuppressive markers like FOXP3 and GATA-3, indicating its potential to boost immune activation by suppressing Treg and Th2 cells. Larger target volumes and higher BED10 values may enhance Th1 responses through TBX21. These findings suggest that SBRT activates the immune system, and its combination with immunotherapy could be promising.